(3HOGjI GdeLJgO hfgGjI GdebJUOs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3eMeO Hf eMeO Hf eMeO Hf YjSi s)
(3ChdgG (B:s
(3Chd GdehLhO efg GdHGH GdKGfi ai ehLHGJ UMI GdfcGM s
(3BNQgG (B:s
(3hCcKQ eG jPcQ GdabgGA QMege Gddg ai GdLhGeY ef cJHge eG TP Yf GdCLfGS GdCQHYI fLR LejY gPG GdOjhGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B228s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdeGdcjs